SARS-CoV-2 Omicron BA.4/BA.5 Mutations in Spike Leading to T Cell Escape in Recently Vaccinated Individuals - Emmelot, Maarten E.; Vos, Martijn; Boer, Mardi C.; Rots, Nynke Y.; van Els, Cécile A. C. M.; Kaaijk, Patricia (Viruses, 2022)
SARS-CoV-2 Omicron (B.1.1.529) lineages rapidly became dominant in various countries reflecting its enhanced transmissibility and ability to escape neutralizing antibodies. Although T cells induced by ancestral SARS-CoV-2-based vaccines also recognize Omicron variants, we showed in our previous study that there was a marked loss of T cell cross-reactivity to spike epitopes harboring Omicron BA.1 mutations. The emerging BA.4/BA.5 subvariants carry other spike mutations than the BA.1 variant. The present study aims to investigate the impact of BA.4/BA.5 spike mutations on T cell cross-reactivity at the epitope level. Here, we focused on universal T-helper epitopes predicted to be presented by multiple common HLA class II molecules for broad population coverage. Fifteen universal T-helper epitopes of ancestral spike, which contain mutations in the Omicron BA.4/BA.5 variants, were identified utilizing a bioinformatic tool. T cells isolated from 10 subjects, who were recently vaccinated with mRNA-based BNT162b2, were tested for functional cross-reactivity between epitopes of ancestral SARS-CoV-2 spike and the Omicron BA.4/BA.5 spike counterparts. Reduced T cell cross-reactivity in one or more vaccinees was observed against 87% of the tested 15 non-conserved CD4+ T cell epitopes. These results should be considered for vaccine boosting strategies to protect against Omicron BA.4/BA.5 and future SARS-CoV-2 variants.